“Double Entry Bookkeeping” Penerapan Basis Persamaan Liabilities Sebagai Komitmen Moral, Kinerja & Tanggungjawab Lembaga Sosial - Husni Mubarak bin Mukhtar; Nur Anita (Inovbiz: Jurnal Inovasi Bisnis, 2019)
This article is focus about double entry bookkeeping (DEB).  Focus assessment of this article is on the develop use of accounting equations Assets = Liabilities + Equity (A=L+E). They which commonly used for approach to understand accounting and development. This concept is a change in equation A = L + E to become A-E = L for transformation from complexcity of transaction. This accounting equiation (A-E = L or L=A-E) just only the consept is for complex understanding and totality frmawork using part of accoutning consept. This article is explent for explioting DEB in usage for public finance, and social institution. The direction of the simplification transformation of this concept is for complex understanding and totality of equations and accounting usage from liabilities.